Pengaruh Indeks Bursa Amerika, dan Bank Indonesia – 7 Days (Reverse) Repo Rate terhadap Indeks LQ45 - Dedy Dedy; Aloysius Hari Kristianto; Rissa Ayustia (Politeknik Negeri Ambon, 2020)
This study aims to determine the effect of the American stock exchange index (DJIA) and the effect of Bank Infonesia – 7 Days (Reverse) Repo Rate or known as BI7dRR on one of the stock indices in Indonesia that has comapnies with high liquidity, namely the LQ45 stock index. The period used as testing data is data derived from the publication of the movement of the Dow Jones Industrial Average and LQ45 stock index and percentage data from Bank Indonesia – 7 Days (Reverse) Repo Rate (BI7dRR) in 2016 – 2019. Data source of this study is a secondary data source obtained through the official stock movement websites (idx.com and nyse.com) as well as Bank Indonesia publications regarding BI7dRR movements. The design of this study uses a quantitative research design using multiple linier regression analysis models so that before testing the model, the data is tested first using classical assumptions. The results of this study indicate that the American Stock Exchange Index (DJIA) is significant and positive for the LQ45 stock index. Meanwhile, BI7dRR has an opposite or negative insignificant direction of influence on the LQ45. The positive influence of the American Stock Exchange Index (DJIA) on LQ45 is due to the fact that the United States is the country with the largest stock index and is the destination country for exports from Indonesia so that growth or movements that occur in America can shake growth in Indonesia. On the other side, BI7dRR is not significant and negative towards the LQ45 stock index, this is because the type of investor in Indonesia is the type who likes to make short-term investments compared to long-term invesments. BI7dRR is a monetary policy in replacing the BI Rate so that at the beginning of its implementation there was a decrese in the percentage of the BI7dRR movement, this was done in order to encourage the domestic economy in accodance with the objectives to be achieved by the government through more optimal credit distribution in the community.